The Effect of Leadership Style and Organizational Culture on Employee Performance at The Regional Secretariat South Sulawesi Province - Fitrawati; Umar Congge (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The purpose of this research is to know the influence of leadership styles and organizational culture on performance Clerk at the Regional Secretariat South Sulawesi province in this study was an employee at the Regional Secretariat South Sulawesi province with the number of samples as much as 85 respondents used to process data. Method of data collection in this study is a questionnaire, interviews and documentation. Methods of data analysis using the method of descriptive and quantitative methods with multiple linear regression analysis used to measure the influence of leadership styles and organizational culture on performance Clerk At the provincial Regional South Sulawesi Secretariat which consists of leadership style and organizational culture. Based on a test of the free variable F (leadership style and organizational culture) together have a positive and significant influence against a variable is bound (the performance of the Employee). Through testing (R) correlation coefficient obtained that level of correlation or relationship between leadership style and organizational culture on performance Clerk is a high relationship that is 93.7%. Organization and culture is the most dominant factor affecting the performance of the employees of the Regional Secretariat In South Sulawesi Province.